C. Wright Mills and the Cuban Revolution : an exercise in the art of sociological imagination - Treviño, A. Javier, 1958- (Envisioning Cuba., 2017)
"A. Javier Treviño reconsiders the opinions, perspectives, and insights of the Cubans that the ... sociologist C. Wright Mills interviewed during his visit to the island in 1960. On returning to the United States, MIlls wrote a small paperback on much of what he had heard and seen, which he published as 'Listen, Yankee: The Revolution in Cuba.' Those interviews - now transcribed and translated - are interwoven here with extensive annotations to explain and contextualize their content. Readers will be able to 'hear' Mills as an expert interviewer and ascertain how he used what he learned from his informants"--